2014
DOI: 10.3390/nu6082987
|View full text |Cite
|
Sign up to set email alerts
|

Association between Intake of Sugar-Sweetened Beverages and Circulating 25-Hydroxyvitamin D Concentration among Premenopausal Women

Abstract: Intake of sugar-sweetened beverages has increased in North America and seems to have several adverse health effects possibly through decreased circulating 25-hydroxyvitamin D (25(OH)D) concentrations. The aim of this cross-sectional study was to evaluate the association between sugar-sweetened beverages intake and 25(OH)D concentrations among premenopausal women. Intake of sugar-sweetened beverages including colas, other carbonated beverages and sweet fruit drinks was assessed using a validated food frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…In this current study, it was found that vit. D was significantly more deficient among carbonated beverages consumers (P≤0.001), this agreed with study in Canada 2014 (26) whom found that women with higher intake beverages had lower concentration of vit. D. carbonated beverages contain a higher concentration of fructose, which derived from corn syrup and used as sweetener.…”
Section: Figure 4 Distribution Of Study Participants By Vitamin D Levelsupporting
confidence: 89%
“…In this current study, it was found that vit. D was significantly more deficient among carbonated beverages consumers (P≤0.001), this agreed with study in Canada 2014 (26) whom found that women with higher intake beverages had lower concentration of vit. D. carbonated beverages contain a higher concentration of fructose, which derived from corn syrup and used as sweetener.…”
Section: Figure 4 Distribution Of Study Participants By Vitamin D Levelsupporting
confidence: 89%
“…Obese people are found to be deficient in vitamin D and it is suggested that due to the sequestering effect of a high quantity of subcutaneous fat, there is reduction in the circulating 25 (OH) vitamin D levels [48]. Another explanation can be that dyslipidemia induces high blood sugar levels that in turn lead to low vitamin D. It has been observed that sugars like fructose decrease the intestinal absorption of 25 (OH) vitamin D levels available through dietary sources [49]. Performing the recommended level of physical activity can be one possible explanation for the association between HDL and vitamin D. There is evidence available that physical activity improves the HDL cholesterol, and it also leads to improvement in the vitamin D levels (especially those doing outdoor activities).…”
Section: Discussionmentioning
confidence: 99%
“…However, these relationships were affected by age, sex, number of pregnancies, parity, birth weight, region of residence, season and location in Jiangsu Province. Children aged 7–23 months with vitamin D deficiency or a low 25(OH)D concentration were more likely to have a daily intake of milk < 500 mL, meat intake > 50.0 g and egg intake ≤ 60.0 g. Children aged 24–71 months with vitamin D deficiency or a low 25(OH)D concentration were more likely to have a daily intake of milk < 300 mL, meat intake > 150.0 g and egg intake ≤ 60.0 g. Duchaine et al 39 suggested that a high intake of sugar‐sweetened beverages may decrease 25(OH)D concentrations in premenopausal women, which is consistent with observations from current research conducted in children aged 0–5 years. Few studies have investigated vitamin D deficiency with meat and the results are controversial.…”
Section: Discussionmentioning
confidence: 99%